Analisis Keberlanjutan Program Mahasiswa pada Program Kampus Mengajar di Yogyakarta - Mir'atun Nur Arifah; Luluk Makrifatul Madhani (EL-TARBAWI, 2022)
Kampus Mengajar is one of the programs from the Merdeka Belajar Kampus Merdeka (MBKM) which was initiated by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia. During the Kampus Mengajar program, students carry out various programs to achieve equity and improve the quality of education in Indonesia. The purpose of this research is to examine how the sustainability of programs that have been initiated by students, after the Kampus Mengajar program is completed. This research will be carried out in several schools located in the Kampus Mengajar in Yogyakarta. The method used in this study is a qualitative method with data collection through interviews, observation, and documentation. The data that has been checked for validity using source triangulation, then analyzed using 3 stages of analysis, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the programs implemented by students generally include 3 aspects, namely: learning programs, administrative programs, and technology adaptation programs. The sustainability of these programs can be classified into 3 levels, namely: the program continues according to the implementation carried out by the students, the program continues with adjustments from the implementers at the school, and the program does not continue after the students complete the Kampus Mengajar program.